2007
DOI: 10.1111/j.1744-7917.2007.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Aphidophagous guilds on nettle (Urtica dioica) strips close to fields of green pea, rape and wheat

Abstract: The common nettle (Urtica dioica L.) is a perennial and cosmopolitan plant species and is known to be the source of food for a great diversity of insects. To understand the importance of the nettle in agro‐ecosystems, a field experiment was carried out in an experimental farm at Gembloux (Belgium) to study the effect of nettle margin strips on aphid and aphidophagous populations in close field crops, namely wheat (Triticum aestivum L.), green pea (Pisum sativum L.) and rape (Brassicae napus L.). The aphids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…There were four species on wheat and broad bean, five and eight on corn and potato, respectively (Table 5). Nevertheless, it is not possible to draw any conclusions about the influence of these differences on the habitat preferences of H. axyridis as in our study and that of Alhmedi et al (2007) no H. axyridis were recorded on wheat, a crop heavily infested with aphids whereas H. axyridis colonizes and reproduces in potato crops that are not infested with aphids (Nault & Kennedy, 2003). Other studies record H. axyridis in the same crops as we studied but at lower densities: 0.02, 0.03 and 0.01 individuals per m² in wheat, potato and corn crops, respectively (Nault & Kennedy, 2003 habitats other than crops indicate that since 2001 the numbers of H. axyridis in Belgium have increased (Adriaens et al, 2008).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…There were four species on wheat and broad bean, five and eight on corn and potato, respectively (Table 5). Nevertheless, it is not possible to draw any conclusions about the influence of these differences on the habitat preferences of H. axyridis as in our study and that of Alhmedi et al (2007) no H. axyridis were recorded on wheat, a crop heavily infested with aphids whereas H. axyridis colonizes and reproduces in potato crops that are not infested with aphids (Nault & Kennedy, 2003). Other studies record H. axyridis in the same crops as we studied but at lower densities: 0.02, 0.03 and 0.01 individuals per m² in wheat, potato and corn crops, respectively (Nault & Kennedy, 2003 habitats other than crops indicate that since 2001 the numbers of H. axyridis in Belgium have increased (Adriaens et al, 2008).…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies on H. axyridis indicate that this species is more frequently found in urban and arboreal habitats (65.6%) than on herbaceous plants (34.4%) (LaMana & Miller, 1996;Adriaens et al, 2008). In addition to arboreal habitats, it is also recorded in field crops such as wheat, corn and potato (LaMana & Miller, 1996;Buntin & Bouton, 1997;Colunga-Garcia & Gage, 1998;Michaud, 2002;Brown, 2003;Nault & Kennedy, 2003;Snyder et al, 2004;Jansen & Hautier, 2008), and also in various natural or semi-natural herbaceous habitats, such as nettle beds, clover or peppermint (LaMana & Miller, 1996;Koch et al, 2006;Alhmedi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations also suggest that this species is now invading (semi-)natural ecosystems in Belgium and is a potential threat to native ladybird species and other aphid predators (Adriaens et al, 2003). Field observations have shown that H. axyridis and E. balteatus often coexist in aphid colonies in different habitats in BelgiumGembloux (Alhmedi et al, 2007). The objective of this study was to obtain a better understanding of the mechanisms that shape guilds of aphidophagous predators and their potential use in biocontrol.…”
Section: Introductionmentioning
confidence: 99%
“…Limonene is known as plant volatile, but also emitted by some aphid species (Francis et al, 2005b Francis et al (2005a) and Verheggen et al (2008) reported the attractiveness of (E)--farnesene to the hoverfly E. balteatus. Results from our study suggest that the use of attractant chemicals, such as limonene, in an agro-system may have the potential to modify the behavioural responses of H. axyridis where the spatial distribution recorded for H. axyridis populations in Belgium was strongly linked to semi-natural habitats (e.g., Alhmedi et al, 2007;Adriaens et al, 2003Adriaens et al, , 2008. The chemical ecology of multitrophic interactions between plants, aphids, and natural enemies has been widely studied for exploitation of beneficial insects in biological control programs (Pickett et al, 1991;Takabayashi & Dicke, 1996;Bottrell & Barbosa, 1998;Thaler, 1999Thaler, , 2002James, 2003a, b;James & Price, 2004).…”
mentioning
confidence: 95%
“…such as deciduous trees, pine trees and various herbaceous habitats (e.g., Adriaens et al, 2003Adriaens et al, , 2008Alhmedi et al, 2007). Therefore, an understanding of the chemical ecology of H. axyridis is essential before developing pest management strategies, first for the efficient use of this species in aphid biocontrol, and second for efficient H. axyridis management programs in agro-ecosystems which could help counter the declines particularly in predator diversity associated with its arrival (Pell, 2008).…”
Section: Introductionmentioning
confidence: 99%